Effect of locally injected autologous platelet-rich plasma on second intention wound healing of acute full-thickness skin defects in dogs - Karayannopoulou, M.; Psalla, D.; Kazakos, G.; Loukopoulos, P.; Giannakas, N.; Savvas, I.; Kritsepi-Konstantinou, M.; Chantes, A.; Papazoglou, L. G. (Veterinary and Comparative Orthopaedics and Traumatology, 2015)
Objectives: Second intention wound healing may be impaired by wound and host factors and thus more advanced therapies are required for a fast and satisfactory outcome. Platelet-rich plasma (PRP), rich in growth factors and cytokines essential for tissue repair, could improve wound healing. The purpose of this experimental study was to evaluate the effect of locally injected autologous PRP on second intention healing of acute full-thickness skin defects in dogs.Methods: Three 2x2 cm full-thickness skin defects were created bilaterally on the dorso-lateral area of the trunk of six Beagle dogs. The wounds of one randomly selected side received PRP treatment, whereas the contra-lateral wounds were left untreated (controls). Wound healing was evaluated by planimetry, laser-Doppler flowmetry measurements of tissue perfusion, and histo-logically.Results: The rate of wound healing did not differ significantly between the two groups. Tissue perfusion was significantly higher in the PRP-treated group (p = 0.008) compared to controls on day 10. Histological evaluation revealed a trend towards greater collagen production and a significantly better collagen orientation (p = 0.019) in PRP-treated wounds on day 20.Clinical significance: Locally injected auto-logous PRP does not accelerate the healing process, but increases tissue perfusion and may promote the formation of organized collagen bundles in acute full-thickness skin defects in dogs.
Keywords: Dog; full-thickness skin defect; platelet-rich plasma; second intention wound healing